(untitled) - Bijlsma, M. (1996)
This book is the study of the technological application of natural processes occuring in our environment. The study of ways in which bio(chemical) processes and reactions can be engineered requires knowledge of a variety of fields, such as chemistry, microbiology, reactor engineering, and reaction kinetics. The term environmental process technology suggests a combination of knowledge of environmental processes and of process technology.
Keywords: Environmental engineering,Kỹ thuật môi trường